2019
DOI: 10.1038/s41598-019-54053-w
|View full text |Cite
|
Sign up to set email alerts
|

G-CSFR antagonism reduces neutrophilic inflammation during pneumococcal and influenza respiratory infections without compromising clearance

Abstract: Excessive neutrophilic inflammation can contribute to the pathogenesis of pneumonia. Whilst anti-inflammatory therapies such as corticosteroids are used to treat excessive inflammation, they do not selectively target neutrophils and may compromise antimicrobial or antiviral defences. In this study, neutrophil trafficking was targeted with a granulocyte-colony stimulating factor receptor monoclonal antibody (G-CSFR mAb) during Streptococcus pneumoniae (serotype 19F) or influenza A virus (IAV, strain HKx31) lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In influenza virus infections, neutrophils may promote clearance, or aggravate pathology, via a feedforward inflammatory circuit 54 , 55 . The cytokine G-CSF and the chemokine CXCL4, which are produced by multiple types of epithelial and endothelial cells of influenza virus-infected lungs, promote neutrophil mobilization from the bone marrow to the inflamed lung 56 , 57 . Several other neutrophil-recruiting chemokines are released by influenza virus-infected epithelial cells, alveolar macrophages and interstitial macrophages (Fig.…”
Section: Leukocytes Recruited To Infected Lungsmentioning
confidence: 99%
“…In influenza virus infections, neutrophils may promote clearance, or aggravate pathology, via a feedforward inflammatory circuit 54 , 55 . The cytokine G-CSF and the chemokine CXCL4, which are produced by multiple types of epithelial and endothelial cells of influenza virus-infected lungs, promote neutrophil mobilization from the bone marrow to the inflamed lung 56 , 57 . Several other neutrophil-recruiting chemokines are released by influenza virus-infected epithelial cells, alveolar macrophages and interstitial macrophages (Fig.…”
Section: Leukocytes Recruited To Infected Lungsmentioning
confidence: 99%
“…For the TGFβ assay in panel (b), n = 8 for all groups. *P < .05, one-way ANOVA versus VEH; # P < .05, one-way ANOVA versus HDMIAV_ISO anti-viral immunity and viral clearance in an acute IAV infection model (Wang, Aloe, et al, 2019). Another potential complication of IAV infections is the increased susceptibility to secondary bacterial infections such as pneumococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, sputum G‐CSF protein levels were significantly higher in asthmatic patients with neutrophil‐dominant inflammation (Kim et al, 2020). We have recently shown that influenza A virus significantly increased blood and lung neutrophil numbers at day 3 post infection in a manner that was suppressed with anti‐GCSFR treatment (Wang, Aloe, et al, 2019). These findings have guided our treatment protocol for this study where anti‐G‐CSFR was delivered during the peak blood granulocytic phase (at days 2 and 5 post influenza infection) as a strategy to block the peak viral‐mediated systemic and local neutrophil response.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jing and colleagues [ 20 ] reported G-CSF increases lung injury in a mouse model of acute renal injury. Wang et al [ 21 , 22 ] reported blocking the G-CSF receptor in mouse models of infection and asthma reduced neutrophil infiltration and neutrophil-mediated inflammation. Tsantikos and associates [ 23 ] reported G-CSF was important in the pathogenesis of chronic obstructive pulmonary disease in some persons.…”
mentioning
confidence: 99%